A study on factors that contribute job satisfaction among MOCCIS’s employees / Nur Faizah Jalaludin - Jalaludin, Nur Faizah (Faculty of Business and Management, 2010)
This research is to study factor that contribute to job satisfaction among MOCCIS employee. It to determine the relationship between job satisfaction with remuneration, working environment and coworker relationship. It started with introduction of the study, which indicates the overall view of what is job satisfaction. Questionnaire where use as the medium to gather the information. There were five sections in this questionnaire, which is demographic, remuneration, coworker relationship, working environment and overall satisfaction, using liked scale method which 1 is strongly disagree and 5 strongly agree. The finding indicates the low strength of significant between job satisfaction and remuneration (0.267) and also low significant strength between job satisfaction and working environment (0.118). Last but not least, researcher proposes recommendation toward situation that occur in MOCCIS.